Comparing the hearing thresholds between master (multiple auditory steady-state response) and pta (pure tone audiometry) in normal hearing and impaired hearing individuals - Nik Adilah, Nik Othman (2008)
Hearing impairment in adults and children need to be identified early and accurately. This is important for the proper implementation of intervention and rehabilitation. The Auditory SteadyState Response (ASSR) has been established as a frequency-specific, objective audiometric procedure, which can provide reliable thresholds to within 5-20 dB of the pure tone behavioural thresholds. And since, its measurements are not influenced by age, it is appropriate to use ASSR for the hearing assessment in children. The aim of the study is to obtain the norms for the population and to compare hearing thresholds obtained by Pure Tone Audiometry (PTA) and by Multiple Auditory Steady-State Response (MASTER) in order to determine the accuracy of MASTER in estimating hearing thresholds for normal hearing and hearing-impaired individuals.A cross-sectional study was conducted in the Audiology Unit, Department of Otorhinolaryngology, HUSM from January to July 2007. A total of forty adults and thirty-four children were involved in the study. They are further divided into normal hearing and hearingimpaired groups. Each subject underwent PTA and MASTER on the same day.The mean threshold difference between PTA and MASTER was 18 dB HL (standard deviation= 8.5) in normal hearing adults and 14 dB HL (SD=6) in normal hearing children. However these values were smaller in the hearing-impaired subjects. The mean threshold difference was 13 dB HL (SD=8.5) in adults and 11 dB HL (SD=6) in children. The PTA and MASTER were highly correlated (r-0.73) and when analysed according to the frequencies, the correlation coefficients of 0.57, 0.52, 0. 77 and 0. 70 for 0.5, 1.0, 2.0 and 4.0 kHz, respectively, shows good correlation. This study confirmed that MASTER is an accurate predictor ofthe PTA thresholds in normal hearing and hearing-impaired subjects.